Opportunities for the use of neuroscience knowledge in the theory of physics education - Červeňová, Daša; Demkanin, Peter (Scientia in educatione, 2023)
In the 20th century, the theory of physics education, like other subject didactics, was significantly influenced by results of the empirical work of psychologists. Certainly, almost every teacher knows names like Piaget, Bruner, Maslow, and every teacher knows Bloom’s taxonomy. Nowadays, it is becoming quite obvious that the theoretical background of the processes taking place while learning physics is moving into the new field called neuroscience, the science of learning, sometimes called the science of mind, brain and education. Teams of neuroscientists equipped with high-quality medical imaging methods seek for the parts of the brain that are undergoing certain operations, how these parts cooperate with each other, and how the findings of psychologists of the 20th century can be explained and refined, or they draw attention to conclusions that appear to be unfounded. This paper elaborates on one of the hypotheses about how our mind works. The hypothesis classifies ways of thinking into five categories, symbols, patterns, ordering, categories, and relationships. Piloting the conscious use of these categories in physics education appears promising and seems to have the potential to improve it through incorporation into textbooks as well as teachers daily work.